Profil pengembangan metakognisi dimensi strategic use pada peserta didik kelas iv sekolah dasar dalam pembelajaran ipas - Dita Maya Angelina; Karsono Karsono; Peduk Rintayati (Didaktika Dwija Indria, 2024)
This study aims to provide an overview of how the strategic utilization dimensions are developed in Grade IV of SDN Karangasem 4 Surakarta. The research employs a qualitative method, including observation, interviews, and document analysis, to gather data. Participants include teachers and students from these classes. Data analysis follows Miles and Huberman's interaction analysis technique. Findings indicate that while there has been some progress in developing the dimensions of strategic use in the IPAS learning process, further optimization is still needed. This study underscores the importance of these dimensions in enhancing children's metacognitive skills. The strategic use dimension helps learners employ appropriate learning strategies for encountered issues. The use of strategies aids learners in easily resolving problems. The implementation of metacognitive dimensions helps learners recognize their own capabilities. Therefore, awareness of metacognition assists learners in completing tasks or solving problems they face. Additionally, learners can easily determine the appropriate learning strategies in the problem-solving process.Keywords : metacognition, strategic use dimensions, science learning, and elementary school